Grafting modification of electrospun polystyrene fibrous membranes via an entrapped initiator in an acrylic acid aqueous solution. Issue 5 (31st May 2012) - Tao, Ran; Zhu, Xinsheng; Zuo, Yu‐Ting; Fan, Li‐Juan; Wang, Bing; Xin, Ji‐Ting
Abstract Ultrafine electrospun polymer fibers, with their large specific surface areas, have not found wide applications partly because the fiber surfaces usually carry an insufficient quantity of active groups. The electrospinning and surface‐grafting copolymerization of polystyrene fibrous membranes were carried out via the embedded radical initiator approach. The results from X‐ray photoelectron spectroscopy show that the initiator added to the polystyrene dope was deliberately expelled onto the fiber surfaces. The microstructure and hydrophilicity of the grafted membranes were investigated with Fourier transform infrared spectroscopy, scanning electron microscopy, and water contact angle and water uptake capacity measurements. An increase in the initiator dosages led to decreases in the grafting rate, water uptake, and hydrophilicity of the grafted membranes; the opposite was true for increases in the neutralization of acrylic acid (AA). However, the grafting, water uptake, and hydrophilicity of the grafted membranes presented nonlinear relationships with the concentration of AA. The initiator emigration technique will provide a facile and feasible platform for the surface‐grafting modification of electrospun membranes. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013